Antiproliferative effects of levan polysaccharide against colorectal cancer cells mediated through oxidative stress-stimulated HOTAIR/Akt signaling pathway: In vitro - Tiancheng Zhan (Elsevier, 2021)
The overexpression of lncRNA HOTAIR can result in cancer progression through upregulation of the Akt signaling pathway. We aimed to evaluate the anticancer effects of levan polysaccharide from Erwinia herbicola on colorectal cancer cells (HT-29) and explore the role of the ROS-mediated HOTAIR/Akt signaling pathway. The HT-29 cancer cells were treated with levan either alone or along with N-acetyl-L-cysteine (NAC), as a potential antioxidant for 24 hrs and different assays including MTT, LDH, ROS, apoptosis, SOD activity, CAT activity, caspase-3 activity, qRT-PCR, and western blot analysis were performed. It was shown that levan treatment induces apparent reduction in cell viability, SOD and CAT activity, HOTAIR expression, the ratio of pAkt protein level and a significant increase in the ROS level, apoptosis induction, and caspase-3 activity, which were effectively suppressed by NAC co-treatment. These data indicated the effective antiproliferative effect of levan on colorectal cancer cells, in which downregulation of ROS-mediated HOTAIR/Akt plays an important role.